Acetylcholine Receptor Stimulation Activates Protein Kinase C Mediated Internalization of the Dopamine Transporter - Underhill, Suzanne M.; Amara, Susan G. (Frontiers in Cellular Neuroscience, 2021)
The dopamine transporter (DAT) clears neurotransmitter from the extracellular space and serves as an important regulator of signal amplitude and duration at sites of dopamine release. Several different intracellular signaling pathways have been observed to modulate DAT activity through regulation of the trafficking of the carriers to and from the cell surface. Acute activation of protein kinase C (PKC) by phorbol esters facilitates clathrin-dependent internalization of the transporter in a variety of model systems; however, the physiological stimuli and cell-surface receptor systems that activate PKC and regulate the DAT in dopamine neurons remain elusive. We report here that stimulation of M1/M5 muscarinic receptors in midbrain cultures decreases the ability of dopamine neurons to transport dopamine through DAT. Carbachol leads to a decrease in DAT activity in primary cultures while the M1/M5-specific antagonist, pirenzepine, blocks these effects. The M3 antagonist, DAU 5884, has no effect, but a positive modulator of M5, VU 0238429, enhances the loss of DAT function in response to carbachol and acetycholine. These data implicate M1/M5 receptors on dopamine neurons in the modulation of DAT function. Bisindolylmaleimide, a PKC inhibitor, blocks the effects of carbachol stimulation on dopamine uptake, supporting a role for PKC in muscarinic receptor-mediated DAT internalization. Furthermore, as shown previously for PKC-induced internalization, downregulation of the DAT is dependent on both clathrin and dynamin. A specific Gq inhibitor peptide also blocks the effects of carbachol on DAT in primary cultures, confirming Gq as the G-protein that couples M1/M5 receptors to PKC activation in these cells. In acute midbrain slices, biotinylation of cell-surface proteins revealed the loss of dopamine transport mediated by muscarinic receptor stimulation was, indeed, due to loss of membrane expression of the DAT in endogenous tissue. These data indicate that stimulation of cholinergic pathways can lead to modulation of dopamine through internalization of the DAT.